The organizational impact of chronic heat: diffuse brood comb and decreased carbohydrate stores in honey bee colonies - Weinberg, Isaac P.; Wetzel, Jaya P.; Kuchar, Eleanor P.; Kaplan, Abigail T.; Graham, Rebecca S.; Zuckerman, Jonah E.; Starks, Philip T. (Frontiers in Ecology and Evolution, 2023)
Insect pollinators are vital to the stability of a broad range of both natural and anthropogenic ecosystems and add billions of dollars to the economy each year. Honey bees are perhaps the best studied insect pollinator due to their economic and cultural importance. Of particular interest to researchers are the wide variety of mechanisms honey bees use for thermoregulation, such as fanning cool air currents around the hive and careful selection of insulated nest sites. These behaviors help honey bees remain active through both winter freezes and summer heatwaves, and may allow honey bees to deal with the ongoing climate crisis more readily than other insect species. Surprisingly, little is known about how honey bee colonies manage chronic heat stress. Here we provide a review of honey bee conservation behavior as it pertains to thermoregulation, and then present a novel behavior displayed in honey bees – the alteration of comb arrangement in response to six weeks of increased hive temperature. We found that while overall quantities of brood remained stable between treatments, brood were distributed more diffusely throughout heated hives. We also found that heated hives contained significantly less honey and nectar stores than control hives, likely indicating an increase in energy expenditure. Our results support previous findings that temperature gradients play a role in how honey bees arrange their comb contents, and improves our understanding of how honey bees modify their behavior to survive extreme environmental challenges.